Relação entre o comportamento agressivo e/ou violento e alterações na neuroimagem : revisão sistemática - Terra, Osmar Gasparini (2009)
Studies of the neurobiology of aggression suggest that, in general, higher levels of aggression are associated with abnormal brain structure and function. However, the relationship between brain abnormalities and aggression has not been studied systematically, but several lines of evidence imply that abnormal function in brain different regions may be associated with aggression and psychopathy. Objective: The aim of our study was to systematically review the reported studies that addressed this topic brain abnormalities and aggression in an effort to clarify the available evidence and develop hypotheses for future studies.Methodological Issues: Medline and PsycINFO data bases from 1987 to 2008 was searched to identify studies of structural and functional brain imaging of persons who engaged in aggressive behavior. The term "violence" was used in many of the articles reviewed, and throughout we use the authors' terminology when describing each study and report the study design. We considered for this review only case-control or cohort studies. In conducting the review, we made an effort to distinguish those studies that included patients with child abuse history. Also, we evaluate case-control studies with (1) aggression-violence possible or probable and (2) functional studies with functional MRI or PET which include activation task of patients with certain or probable aggressive behavior.Results: Our search identified 30 published studies (29 case-control and 01 cohort) comparing structural brain imaging of violent and nonviolent persons. Some results are inconsistent and contradictory. This situation is primarily due to varying definitions of violence, characteristics of the samples, and the use of different measures to tap neurobiological correlates of violent behavior. The samples in the studies reviewed were generally small, for instance some studies did not include a comparison group of healthy participants. Conclusion: In conclusion, our review highlights evidence that among people with violent or antisocial behavior as compared with those with no such history, had abnormalities in different brain areas most in the frontal lobes including the orbito-frontal, pre-frontal and anterior cingulated cortex among others. These findings also indicate the necessity of future researches taking account not only of the onset and persistence of the aggressive behavior but also gender of the protagonist, child abuse history and larger and more homogeneous samples.